Theorizing Japanese FDI to China - Rahman, Khondaker (Journal of Comparative International Management)

(untitled) (Management Futures, 2006)
Using mainly archival data, this paper examines the nature and causes of Japanese foreign direct investment (FDI) to China and theorizes it with inductive arguments. It proceeds as follows. After a brief introduction on China’s robustness in the global investment market, it introduces the position of Japan as investor in this country, and proceeds with an examination of the major theories of FDI. It then examines the underlying causes of Japanese FDI to China in view of those theories. The paper concludes that, in addition to many investment-alluring incentives, most prominently China over time has infused, fostered, created, and nurtured numerous competitive advantages (pull-factors) within its investment proliferating environment, which ultimately ushered FDI from Japan to it. Domestic factors as well as global investment competitors drive (push-factors) toward China further induced Japanese multinational corporations (MNCs) to boost investment into China.